ASSOCIATION BETWEEN MEDICATION ADHERENCE AND QUALITY OF LIFE AMONG OUTPATIENTS WITH TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2026)
Objective: To assess health-related quality of life and analyze the association between medication adherence and quality of life among outpatients with type 2 diabetes.Subjects and methods: A cross-sectional descriptive study was conducted among 379 outpatients with type 2 diabetes. Quality of life was assessed using the 15D instrument, while medication adherence was measured using the 8-item Morisky Medication Adherence Scale. Diabetes self-care behaviors were evaluated using the Summary of Diabetes Self-Care Activities scale. Data were analyzed using SPSS version 22.0 with descriptive statistics and regression analyses.Results: The mean 15D quality-of-life score was 0.9 ± 0.1 points. The lowest domain score was observed for sexual activity (0.3 ± 0.2 points), followed by vision (0.8 ± 0.2 points). Analyses showed that the likelihood of non-adherence decreased as overall quality-of-life scores and domains such as sleep, vitality, depression, and sexual activity improved (p < 0.05).Conclusion: Overall quality of life among outpatients with type 2 diabetes in this study was relatively high. Medication adherence was associated with quality of life and diabetes self-care behaviors. Strengthening interventions to improve medication adherence may contribute to better quality of life and more effective diabetes management.
Keywords: Type 2 diabetes, medication adherence, quality of life, 15D instrument, outpatient care.